The Use of Complaints in the Inter-Language of Turkish EFL Learners - Deveci, Tanju (Colombian Applied Linguistics Journal, 2010)
Many Turkish EFL learners struggle with giving complaints and criticisms in the EFL classroom. Language instructors must find way to provide students with the linguistic and pragmatic elements of EFL to be able to appropriately complain as EFL users. The purpose of this study is to investigate the complaint speech used by Turkish EFL learners in two different situations: speaking to a commiserating teacher and speaking to a contradicting teacher. Four kinds of data sources were used to collect data in the classroom: twenty native English speakers’ role-plays, twenty-five Turkish native speakers’ role-plays, and forty students’ role-plays. The subjects’ complaint speech act sets were a coding scheme borrowed from a previously conducted study by Murphy and Neu (1996). The baseline and the inter-language data were compared to see to what extent they were similar or different, whether or not the Turkish EFL learners made positive and negative transfer, and if there were any features unique to the inter-language of the learners. The findings revealed that when speaking to the commiserating teacher, students made both positive and negative transfer in using ‘demand’. The students speaking to the contradicting teacher made positive transfer in the components ‘explanation of purpose’, ‘complaint’ and ‘justification’. The component ‘demand’ was subject to negative transfer.